Building successful teams - Curtis Butler and Associates (Watertown, Md. : American Management Association, 1991)
The video is primarily for team leaders and facilitors, management and steering committees. Emphasize the necessity for communication links between teams and top management and the need to align team goals with the strategic vision of the organization
Keywords: Work groups; Quality circles